Prevalence of microalbuminuria and its correlates among diabetic patients attending diabetic clinic at National Guard Hospital in Alhasa - Aneesah A AlFehaid (Wolters Kluwer Medknow Publications, 2017)
Introduction: Diabetes mellitus is one of the most common diseases encountered in clinical practice. Diabetic nephropathy is a common consequence of long-standing diabetes mellitus; microalbuminuria (MA) is considered an early stage of diabetic nephropathy. Objectives: To determine the prevalence of miciroalbuminuria in diabetic patients and factors associated with MA. Materials And Methods: This cross-sectional study was conducted in the diabetic clinic of the primary health center of the National Guard Hospital. Diabetes type 2 patients between the ages of 20-60 years who attended the clinic in 2012 were included in this study. Data were collected by reviewing medical records for demographic and disease-related variables. MA was detected by measuring the albumin to creatinine ratio, and MA was diagnosed if this ratio was between 30 and 300 mg/g on two occasions. Results: MA was found in 37.4% of the sample and the rate was significantly higher among females (P < 0.027). MA was positively related to body mass index (BMI) (P < 0.002), the presence of hypertension (P < 0.000), duration of diabetes (P < 0.000), glycated hemoglobin (P < 0.000), fasting plasma glucose (P < 0.000), and low-density lipoprotein (LDL) (P < 0.043). No statistically significant correlation was found between MA and age, creatinine level, high-density lipoprotein, and triglyceride. Conclusion: The prevalence of MA in patients with diabetes in this study was high. The study suggests the need to screen for MA early, and the active management of modifiable risk factors, in particular, hyperglycemia, hypertension, LDL, and BMI, to reduce the burden of future end-stage renal disease.